Hepatocellular Carcinoma with Inferior Vena Cava Thrombus in a Child - Pratiwi, Fauziah; Prihaningtyas, Rendi Aji; Setyoboedi, Bagus; Ontoseno, Teddy (Current Internal Medicine Research and Practice Surabaya Journal, 2024)
Hepatocellular carcinoma (HCC) in children is the second common malignant liver tumor after hepatoblastoma. Chronic hepatitis B virus (HBV) infection causes most hepatocellular cancer worldwide. Metastases to the inferior vena cava (IVC) and right atrium (RA) tumor thrombi are even less common. We reported a case of a 13-year-8-month-old girl with HCC and IVC involvement. Vascular invasion predicts poor overall survival in HCC patients. Patients with HCC involving the IVC had a higher risk of sudden mortality and a poor treatment outcome. It is difficult to treat, and no standard therapy has been established. This case report aimed to describe HCC with IVC involvement. This is a rare disease with a poor prognosis, therefore it is important to detect and manage early.